Lightweight cryptography system for IoT devices using DNA. (October 2021) - Al-Husainy, Mohammed Abbas Fadhil; Al-Shargabi, Bassam; Aljawarneh, Shadi
Abstract: Many lightweight encryption algorithms have been developed for tackling the limitations of resources on the Internet of Things (IoT) devices. Such devices have limited processing capabilities in terms of speed, storage, and memory. In this paper, we designed and implemented a flexible lightweight encryption system with strong and simple substitution, and transposition operations to encrypt and decrypt data that meets limited processing capabilities within IoT devices. We used a variable block size to make the proposed system more flexible to be implemented on various IoT devices that have different memory sizes. Besides, the DeoxyriboNucleic Acid (DNA) sequence is utilized to generate random encryption keys that make it hard to break by the criminals. The experimental results of the proposed lightweight encryption system show promising results to be used for any IoT device with respect to memory size and encryption time compared to well-known cryptographic systems. This is achieved by using variable block size to minimize the size of memory use and minimizing the encryption time by using logical and rotate operations. For fulfilling the security goals, the developed lightweight encryption system has shown a better avalanche effect value which is over 50% compared to other existing encryption systems. The avalanche effect proves that such system is capable to secure IoT data against real-time attacks. Graphical abstract: Image, graphical abstract